Inequalities in child immunization coverage in Ghana: Evidence from a decomposition analysis - Derek Asuman; Charles Godfred Ackah; Ulrika Enemark (Health Economics Review, 2018)
Childhood vaccination has been promoted as a global intervention aimed at improving child survival and health, through the reduction of vaccine preventable deaths. However, there exist significant inequalities in achieving universal coverage of child vaccination among and within countries. In this paper, we examine rural-urban inequalities in child immunizations in Ghana. Using data from the recent two waves of the Ghana Demographic and Health Survey, we examine the probability that a child between 12 and 59 months receives the required vaccinations and proceed to decompose the sources of inequalities in the probability of full immunization between rural and urban areas. We find significant child-specific, maternal and household characteristics on a child's immunization status. The results show that children in rural areas are more likely to complete the required vaccinations. The direction and sources of inequalities in child immunizations have changed between the two survey waves. We find a pro-urban advantage in 2008 arising from differences in observed characteristics whilst a pro-rural advantage emerges in 2014 dominated by the differences in coefficients. Health system development and campaign efforts have focused on rural areas. There is a need to also specifically target vulnerable children in urban areas, to maintain focus on women empowerment and pay attention to children from high socio-economic households in less favourable economic times.
Keywords: 330; Immunization coverage; Childhood; Vaccination; Health inequality; Decomposition; Rural-urban; Ghana